Efektivitas Penyebaran Informasi Publik Melalui Website oleh Dinas Komunikasi dan Informatika Kabupaten Ngada - Marselinus Salvator; Nanang K. Heremba (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2023)
Nowadays the internet makes the information spread very fast. It makes information easy to be accesd. In Indonesia it is very important in maximizing public oversight to make good, clean and transparent governance. The Ngada Regency Government through the Department of Communication and Information has used the website as a means of disseminating Information. Then, this research was conducted to find out how the “EFFECTIVENESS of DISTRIBUTION OF PUBLIC INFORMATION THROUGH THE WEBSITE BY THE COMMUNICATION AND INFORMATICS DEPARTMENT OF NGADA REGENCY”. This study aims to analyze and describe the effectiveness of public information dissemination through the website, find out what are the inhibiting factors in its implementation, and see the efforts made by the Ngada Regency Communication and Information Office in dealing with the obstacles experienced. This study uses a qualitative method with a descriptive approach. The data collection technique used is triangulation; interviews, observations, and documentation. The data analysis technique uses data reduction, data presentation, and drawing conclusions.